Debt maturity and institutions: Does creditor protection matter? - Ghada Tayem (Economies, 2023)
This study aims to investigate the relationship between creditor protection and the debt maturity structure of corporations in the Gulf Cooperation Council (GCC) countries. The GCC countries enjoy large GDPs, growing capital markets, especially the Islamic bonds (Sukuk) market, and negligible tax environments. Nonetheless, the GCC countries' financial systems are still dominated by banks, and their private investments are held by concentrated investors. The study utilizes firm-level financial data and country-level institutional data obtained from the World Bank Governance Indicators and Doing Business databases and applies the two-stage least square estimator to test its hypotheses. The findings indicate that stronger regulatory effectiveness is associated with long debt maturities, while better creditor protection is associated with short debt maturities. The latter finding suggests that managers and owners have incentives to utilize short-term debt in economies characterized by stronger liquidation and insolvency rules to avoid the loss of control in the case of a firm default. This finding has policy implications in terms of the importance of considering the dual influence of institutional reforms on the supply of and demand for long-term capital.
Keywords: 330; creditor protection; debt maturity; GCC countries; institutions; long-term debt